Involvement of global genome repair, transcription coupled repair, and chromatin remodeling in UV DNA damage response changes during development. - Hannes Lans; Jurgen A Marteijn; Björn Schumacher; Jan H J Hoeijmakers; Gert Jansen; Wim Vermeulen (PLoS Genetics)
Nucleotide Excision Repair (NER), which removes a variety of helix-distorting lesions from DNA, is initiated by two distinct DNA damage-sensing mechanisms. Transcription Coupled Repair (TCR) removes damage from the active strand of transcribed genes and depends on the SWI/SNF family protein CSB. Global Genome Repair (GGR) removes damage present elsewhere in the genome and depends on damage recognition by the XPC/RAD23/Centrin2 complex. Currently, it is not well understood to what extent both pathways contribute to genome maintenance and cell survival in a developing organism exposed to UV light. Here, we show that eukaryotic NER, initiated by two distinct subpathways, is well conserved in the nematode Caenorhabditis elegans. In C. elegans, involvement of TCR and GGR in the UV-induced DNA damage response changes during development. In germ cells and early embryos, we find that GGR is the major pathway contributing to normal development and survival after UV irradiation, whereas in later developmental stages TCR is predominantly engaged. Furthermore, we identify four ISWI/Cohesin and four SWI/SNF family chromatin remodeling factors that are implicated in the UV damage response in a developmental stage dependent manner. These in vivo studies strongly suggest that involvement of different repair pathways and chromatin remodeling proteins in UV-induced DNA repair depends on developmental stage of cells.